2018
DOI: 10.1016/j.exphem.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 expression and function in AML: An evolving paradigm

Abstract: Acute myeloid leukemia (AML) arises when immature myeloid blast cells acquire multiple, recurrent genetic and epigenetic changes that result in dysregulated proliferation. Acute leukemia is the most common form of pediatric cancer, with AML accounting for ~20% of all leukemias in children. The genomic aberrations that drive AML inhibit myeloid differentiation and activate signal transduction pathways that drive proliferation. MicroRNAs, a class of small (~22 nucleotide) noncoding RNAs that posttranscriptionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…A consistent and strong association of miR-155 overexpression with poor prognosis in pediatric AML was also confirmed[ 110 - 112 ]. An interesting relationship between the level of expression of miR-155, its biological function and prognosis in AML was noted by Narayan et al[ 105 , 111 ]. Researchers conducted experiments on cells obtained from patients diagnosed with AML and on a murine model, where they found that between 10- and 50-fold overexpression of miR-155 (plays the role of oncogene) is associated with poorer OS and increased tumor burden.…”
Section: Role Of Microrna In Outcome Predictionmentioning
confidence: 98%
See 2 more Smart Citations
“…A consistent and strong association of miR-155 overexpression with poor prognosis in pediatric AML was also confirmed[ 110 - 112 ]. An interesting relationship between the level of expression of miR-155, its biological function and prognosis in AML was noted by Narayan et al[ 105 , 111 ]. Researchers conducted experiments on cells obtained from patients diagnosed with AML and on a murine model, where they found that between 10- and 50-fold overexpression of miR-155 (plays the role of oncogene) is associated with poorer OS and increased tumor burden.…”
Section: Role Of Microrna In Outcome Predictionmentioning
confidence: 98%
“…MiR-155 is evolutionarily conserved, and as an inhibitor of lineage differentiation, it is one of the most critical regulators of posttranscriptional gene expression in B cells[ 101 , 102 ]. It has also been confirmed to be associated with pathogenesis, aggressiveness and progression in CLL[ 103 , 104 ]; poor survival in adult and pediatric AML[ 105 ]; and poor clinical prognosis in Hodgkin's lymphomas[ 106 ] and B-cell-type Diffuse large B-cell lymphoma[ 107 , 108 ]. El-Khazragy et al[ 109 ] tried to connect the upregulation of miRNA-155a and miRNA-181a expression to ALL outcome.…”
Section: Role Of Microrna In Outcome Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Altered expression of miR-155 has been reported in several hematologic malignancies 2, 6-10, including diffuse large B-cell lymphoma (DLBCL), Hodgkin's lymphoma (HL), follicular lymphoma (FL), acute myeloid leukemia (AML), acute and chronic lymphoblastic leukemia (ALL, CLL), and myelodysplastic syndrome (MDS). Upregulated miR-155 expression was further associated with tumor progression and poor prognosis in several reports.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are small (19–23-nt in length) non-coding regulatory RNAs that regulate the stability and/or translation of their target transcripts. MicroRNAs have been progressively implicated in all aspects of cell biology and homeostasis and established as key players in a number of pathologies, including, but not limited to, inflammatory, metabolic and cardiovascular diseases, neuropathologies, and cancers [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%